Some notes on a variability of Bothriolepidids (Placodermi, Antiarchi): unusual specimen of Livnolepis Heckeri (Luksevics) from the famennian of Tver region, European Russia - S. V. Moloshnikov; V. V. Linkevich (Известия высших учебных заведений: Геология и разведка, 2019)
The fragment of the skull cap of placoderm Livnolepis heckeri (Luksevics) from the Bilovo Formation (Famennian, Upper Devonian) near the Bilovo Village of Tver Region has been described. The character of the passage of sensory grooves on its external surface is unusual as for this species as for all other bothriolepidids. The oblique cephalic pit-line (or central sensory) groove normally passes from the nuchal on the lateral bones. The left branch of the obhque cephalic pit-line groove on the studied specimen runs from the nuchal onto the paranuchal and only then on the lateral. The right branch of this pit-line groove reaches the posterolateral margin of the nuchal, passes along the suture between the nuchal and paranuchal and then transfers into the lateral bone. The branches of the obhque cephalic pit-line groove are subparallel to the posterior margin of the nuchal bone in the Bilovo specimen. The pit-line grooves, which run parallel and subparallel to the posterior margin of the nuchal and anteriorly to the supratemporal (supraoccipital) cross-commissural pit-lines, were earlier determined in some bothriolepidids {Bothriolepis cellulosa (Pander), B. paradoxa (Agassiz) and others) as the middle grooves but not the obhque cephalic. The paranuchalswith the obhque cephalic pit-line grooves were earlier unknown. The unusual character of the passage of the sensory lines is refered to the individual variability in the exoskeleton of L. heckeri. Types of the bothriolepidid exoskeletal variability have been briefly considered. The passage of the pit-line grooves on the external surface of the bothriolepidid and asterolepidid skull roofs has been discussed.